Una aproximación al estudio del Derecho Internacional Público - Franciskovic Ingunza, Millitza (2019)
This article aims to bring the reader closer to an analysis referring to the object of study of Public International Law, from the various definitions that have been developed on this discipline, as well as to understand the differences between the internal rights of the States with the Law International Public, we will also cover the various denominations that have been given to this discipline and how it is divided from a methodological point of view